Advances in proton therapy in lung cancer. (14th July 2018) - Vyfhuis, Melissa A.L.; Onyeuku, Nasarachi; Diwanji, Tejan; Mossahebi, Sina; Amin, Neha P.; Badiyan, Shahed N.; Mohindra, Pranshu; Simone, Charles B.
Lung cancer remains the leading cause of cancer deaths in the United States (US) and worldwide. Radiation therapy is a mainstay in the treatment of locally advanced non-small cell lung cancer (NSCLC) and serves as an excellent alternative for early stage patients who are medically inoperable or who decline surgery. Proton therapy has been shown to offer a significant dosimetric advantage in NSCLC patients over photon therapy, with a decrease in dose to vital organs at risk (OARs) including the heart, lungs and esophagus. This in turn, can lead to a decrease in acute and late toxicities in a population already predisposed to lung and cardiac injury. Here, we present a review on proton treatment techniques, studies, clinical outcomes and toxicities associated with treating both early stage and locally advanced NSCLC.